Market value chain of Carapa procera oil and its contribution to income and poverty alleviation in Mali. Issue 4 (2nd October 2019) - Dembélé, Urbain; Koné, Yénizié; Lykke, Anne Mette; Témé, Bino; Kouyaté, Amadou Malé
ABSTRACT: The aim of this study was to characterize the local market part of the value chain of Carapa procera oil in Mali. The data were collected in four local markets using semi-structured individual interviews, focus groups and participant observations. Three sources of oil supply were identified, one national and two from neighbouring countries. Semi-wholesalers obtained the highest profit margins per litre. Four marketing channels were identified, and the profit margins of traders varied depending on the channel. The market concentration ratio showed an oligopoly market structure, indicating that the market was not competitive. The average annual income of traders was US 221.53, which represented 63.3% of the poverty threshold estimated at US 350 in 2016 in Mali. However, there is a potential for much higher gains and a more efficient marketing system. Knowledge about the structure and distribution of profits and margins along the market part of the value chain provides information to policy makers about the potential for improving the income of traders and other actors and also highlights the opportunities that the marketing of oil could contribute to local and national economies.